Efficiency of Friction Pendulum Bearings in Vertically Irregular Structures Subjected to Various Types of Earthquakes - Jamal Ghazi Al Adwan; Salam Al Kasassbeh; Jafar Al Thawabteh; Bilal Yasin; Yazan Alzubi (Civil Engineering Journal, 2022)
The attention towards seismic mitigation using passive control systems has increased significantly over the last few decades to reduce earthquake demands and achieve the required performance objectives. Nowadays, friction pendulum bearings have proven efficient in mitigating regular RC structures subjected to a wide range of earthquakes. Nonetheless, limited studies were dedicated to investigating the performance and efficiency of this type of isolation system utilized in RC structures with various types of vertical irregularities. Besides, comprehensive parametric assessments that investigate the behavior of structures supported on friction pendulum bearings subjected to pulse-like and non-pulse-like earthquakes are scarce. Thus, this study aims to assess the behavior of RC frames equipped with friction pendulum isolators under different types of earthquakes. In the context of the paper, three types of vertical irregularities, known as soft-story, heavy-story, and stepped structures, will be modeled and investigated. Moreover, the outcomes of these buildings will be benchmarked to a regular model to illustrate the efficiency of the selected isolation systems. Furthermore, the performance of the base-isolated buildings with friction pendulum isolators subjected to pulse-like and non-pulse-like earthquakes will be reported. In general, the study results have shown that pulse-like earthquakes exhibited higher values than non-pulse-like earthquakes for the different responses of the structures at the periods of 2.5 and 3 and the damping ratios of 15%, 20%, and 25%. Doi: 10.28991/CEJ-2022-08-09-05 Full Text: PDF